Conversion of Douglas Dakota G-AMZE for Smith autopilot type D development - Firth, A. (College of Aeronautics, 1953)
Dakota K.J. 874 was delivered as a standard R.A.F Mark IV paratrooping aircraft. The undermentioned modifications were called for in order, to convert it to an aircraft suitable for the carrying out of flight tests & development on the Type "D" Auto Pilot", bearing in mind the lessons learned from previous operations of a Valetta on similar work. The requirement that the aircraft be placed in a civil category for maintenance entailed the conversion being carried out by a Firm approved by the Air Registration Board for overhaul and maintenance, including Radio, also approved for Design. After discussion, the contract was placed with the College of Aeronautics, Cranfield, whose maintenance and design organization is fully A.R.B. approved, the aircraft being delivered during February, 1953. The first requirement was the removal of all surplus equipment from the airframe. This included all the paratrooping gear, the seating, which was unsuitable since it ran the full length of the fuselage facing towards the centre gangway, the glider towing attachment in the tail cone, the Behdix W.T. radio gear and the A.3 Auto Pilot. The Bendix Radio was not wanted because it was too bulky and would not be used in connection with Type "D" trials, and it was also intended to operate the Dakota without a wireless operator. The A.3 Auto Pilot was to be removed complete, including the Servo Motors which Were in series with the main control cables, so that no servicing of these components would be required under operating conditions ...[cont.].